Enhancement of Cement’s Compressive Strength of Concrete using Mid-infrared Ray – A fundamental research (Global Journals of Research in Engineering, 2024)
Concrete is one of the most versatile material in building construction Overall quality of cement is indicated by the compressive concrete strength of concrete CSC Many techniques are available to increase the CSC As one of the technology we irradiated the cement with mid-infrared rays and observed 38 CSC increase This technology is economical rapid easy user-friendly can be used by manufacturer to client and in future may gain vast scope and utility in civil engineering
Keywords: cement; mid-infrared; irradiation; compressive strength of concrete; increase; safe; economical